(untitled) (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2019)
The paper studies the configuration of the maid, a character in Carmen Laforet’s novels. Three novels are analysed: Nada, La isla y los demonios and La insolación. Based on a theorical support about the character in narrative, the techniques of the characterization of the corresponding maids will be examined, in order to characterize the guidelines of a structural and stylistic evolution of the writer, so that it will be possible to outline this specific category of character. Key words: Carmen Laforet, maid, literary character.